An Approach to Confederate Training Within the Context of Simulation-Based Research. Issue 5 (October 2016) - Adler, Mark D.; Overly, Frank L.; Nadkarni, Vinay M.; Davidson, Jennifer; Gottesman, Ronald; Bank, Ilana; Marohn, Kimberly; Sudikoff, Stephanie; Grant, Vincent J.; Cheng, Adam
Abstract : Summary Statement: Simulation-based education often relies on confederates, who provide information or perform clinical tasks during simulation scenarios, to play roles. Although there is experience with confederates in their more routine performance within educational programs, there is little literature on the training of confederates in the context of simulation-based research. The CPR CARES multicenter research study design included 2 confederate roles, in which confederates' behavior was tightly scripted to avoid confounding primary outcome measures. In this report, we describe our training process, our method of adherence assessment, and suggest next steps regarding confederate training scholarship.